2014
DOI: 10.1007/s12149-014-0921-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a computer-assisted diagnosis system, BONENAVI version 2, for bone scintigraphy in cancer patients in a routine clinical setting

Abstract: BONENAVI version 2 is an effective computer-assisted diagnosis system for bone scanning, but the drawbacks of bone scanning remain unresolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 14 publications
2
30
0
1
Order By: Relevance
“…The Japanese version of this software, BONENAVI (FUJIFILM RI Pharma, Tokyo, Japan), was modified using a cohort of Japanese patients [8, 9], and revised [11]. In the present study, we used ANN obtained using BONENAVI version 2.1.7. to analyze diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Japanese version of this software, BONENAVI (FUJIFILM RI Pharma, Tokyo, Japan), was modified using a cohort of Japanese patients [8, 9], and revised [11]. In the present study, we used ANN obtained using BONENAVI version 2.1.7. to analyze diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings mean that the ANN value and sensitivity of BONENAVI are robust for the various CT types. We formerly reported that the ANN and sensitivity of BONENAVI were not different among the CT types in breast cancer or lung cancer patients with skeletal metastasis [9]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each individual hot spot was classified either as a metastasis or not as a metastasis by using an artificial neural network, and the BSI was calculated as the percentage of the sum of all hot spots classified as bone metastases using the artificial neural network values. To calculate BSI, we used Bonenavi version 2 (Fujifilm RI Pharma Co. Ltd., Tokyo, Japan; Exini Bone, Exini Diagnostics, Lund, Sweden) [11].…”
Section: Bone Scan Indexmentioning
confidence: 99%